Patent citations indicating present value of the biotechnology business - Tuomo Nikulainen; Raine Hermans; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2006)
Patents form a central pathway for capturing the value of intangible assets in a knowledge-intensive business. Patents can potentially generate and support earnings in two ways: they can be traded or licensed out, and they can provide critical protection for core production technologies or products that are to be traded. Recent patent valuation literature relates backward citations to the basicness of an innovation, and forward citation counts to the economic value of an innovation. In our data covering all Finnish biotechnology patents, we found indications of only the first relation. This might reflect either an excess of a technologyorientated attitude of the companies, or a well-argued value creation mechanism that remains hidden from our research methods. The results imply that a usage of patent citation measures might provide important measures for innovation policies, technology management, and valuation of knowledge-intensive industries.
Keywords: O30; M21; L25; 330; Patents; Patent Citations; Biotechnology; Biotechnische Industrie; Patent; Wissenstransfer; Innovationsdiffusion; Publikationsanalyse; Finnland